1996
DOI: 10.1128/iai.64.5.1879-1883.1996
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibody responses of cattle following experimental infection with Escherichia coli O157:H7

Abstract: Oral inoculation of calves and steers with 10 10 CFU of Escherichia coli O157:H7 induced prompt and sustained increases in serum antibodies to O157 lipopolysaccharide. Neutralizing antibodies to verotoxin 1 also increased rapidly in most steers but more gradually in calves. None of the animals developed neutralizing antibodies to verotoxin 2. These serological responses were not correlated with elimination of infection in calves or steers or protection of calves against reinfection with the same strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…Calves have been shown to seroconvert strongly and persistently to O157 antigen following experimental infection with E. coli O157:H7 (19). The effect of seroconversion to O157 on B. abortus serology was recognized by Stuart and Corbel, who described positive B. abortus agglutination tests with sera from rabbits immunized against E. coli O157 as well as with sera from cattle experimentally infected with E. coli O157 (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Calves have been shown to seroconvert strongly and persistently to O157 antigen following experimental infection with E. coli O157:H7 (19). The effect of seroconversion to O157 on B. abortus serology was recognized by Stuart and Corbel, who described positive B. abortus agglutination tests with sera from rabbits immunized against E. coli O157 as well as with sera from cattle experimentally infected with E. coli O157 (29).…”
Section: Discussionmentioning
confidence: 99%
“…Given the intermittent nature of fecal shedding in cattle and the limited duration of shedding in humans, it is logical that other diagnostic techniques, such as serology, might be useful adjuncts to bacteriologic culture methods for detecting infection with E. coli O157:H7. Both cattle and humans seroconvert to O157 antigen following oral infection with E. coli O157:H7 (2,19). Several studies have demonstrated the utility of anti-O157-antibody detection in cases of hemorrhagic colitis and hemolytic uremic syndrome where bacteriologic culture failed to detect O157:H7 in feces (4,7,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The wbdP gene encodes a glycosyl transferase that is involved in modifying the surface LPS of the bacterium and has also been identified previously by Dziva et al as being required for intestinal colonization in calves by E. coli O157:H7 (Dziva et al, 2004). It is well known that cattle, and presumably sheep, make antibodies against the O157 LPS following experimental inoculation (Johnson et al, 1996 ). However, it is not clear how the LPS is involved in host colonization.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that an effective stimulation of both systemic and local responses will be required and particularly stimulation of IgA responses that play a key role in the immune protection of mucosal surfaces and provides an important line of defense against invading pathogens (Fagarasan & Honjo, 2003;Hamburger et al, 2006). Previous work in cattle has reported serological IgG responses against a variety of antigens following E. coli O157 colonization (Cray & Moon, 1995;Pirro et al, 1995;Laegreid et al, 1999;Wray et al, 2000;Potter et al, 2004), and IgA responses against E. coli O157:H7 intimin have been detected in nasal secretions following nasal inoculation during a vaccine trail (Johnson et al, 1996;Yokomizo et al, 2002). Nevertheless, there is little information on the gastrointestinal mucosal humoral response to E. coli O157:H7, in particular following colonisation of the terminal rectum.…”
Section: Introductionmentioning
confidence: 99%